Trichotillomania Below Two Year Of Age - Brar Balwinder Kaur; Pall Anuj; Gupta Rajesh Rani (Wolters Kluwer Medknow Publications, 2003)
Trichotillomania is the compulsive habit that induces an individual to pluck hair repeatedly. Psychotherapy or psychoanalysis offers the best long-term prognosis for trichotillomania. We report two cases of trichotillomania in children less than two years of age because of its rarity.